Spherical Nucleic Acids 2020
DOI: 10.1201/9781003056713-106
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Nucleic Acid Nanoparticle Conjugates as an RNAi-Based Therapy for Glioblastoma*

Abstract: have interest in AuraSense Therapeutics, which develops SNAbased technologies. The content is solely the responsibility of the authors and does not necessarily represent the official views of the sponsors or government, and no official endorsement should be inferred. Data and materials availability: SNA conjugates and Bcl2L12-related biologicals are available upon request from C.A.M. and A.H.S. with an executed materials transfer agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 13 publications
3
99
0
Order By: Relevance
“…Spherical nucleic acids (SNAs) are clinically used nanoparticle conjugates consisting of densely packed, highly oriented, therapeutic oligonucleotides (immune-modulatory, antisense, and siRNA gene regulatory) surrounding a nanoparticle core (24)(25)(26)(27). SNAs, unlike their linear cousins, possess the ability to enter cells without the need for auxiliary transfection reagents.…”
Section: Significancementioning
confidence: 99%
“…Spherical nucleic acids (SNAs) are clinically used nanoparticle conjugates consisting of densely packed, highly oriented, therapeutic oligonucleotides (immune-modulatory, antisense, and siRNA gene regulatory) surrounding a nanoparticle core (24)(25)(26)(27). SNAs, unlike their linear cousins, possess the ability to enter cells without the need for auxiliary transfection reagents.…”
Section: Significancementioning
confidence: 99%
“…They showed that the gene silencing can be temporally and spatially controlled using a pulsed NIR laser via lightinduced siRNA release. Jensen et al [27] complexed a high-density monolayer of siRNA on the surface of gold nanoparticles, a nanostructure so-called spherical nucleic acid (SNA), to knockdown the expression of oncoprotein Bcl2Like12 (Bcl2L12) of glioma cells. The in vitro studies showed SNAs accumulated in human glioma U87MG cells efficiently and neutralized Bcl2L12, a potent caspase and p53 inhibitor specifically overexpressed by the majority of human primary gliomas, without any chemical modifications and auxiliary transfection methods.…”
Section: Noble and Precious Metals -Properties Nanoscale Effects Andmentioning
confidence: 99%
“…Gold NPs can be in the form of nanorods, branched, nanostars, nanoclusters, nanocubes, nanospheres, nanoshells, and nanoroses, and the surfaces of these NPs can be modified to be useful for dark field imaging, photothermal therapy fluorescence imaging, drug loading, gene delivery, antigen binding, and linking to other entities. 36,37 Of the various forms of gold NP, a couple have shown enough promise to be used in clinical trials 38,39 . Of all inorganic NPs, iron oxide nanoplatforms have shown the most clinical translatability because they can be used to effectively deliver iron to treat anemia.…”
Section: Inorganic Nanoparticlementioning
confidence: 99%